A cross-sectional study determining the prevalence of musculoskeletal diseases in automotive factory workers: Occupational musculoskeletal diseases - Sirzai , Hulya; Dundar , Emine Ahi (Journal of Surgery and Medicine, 2022)
Background/Aim: Work-related musculoskeletal disorders (WMSDs) develop due to exposure to physical and psycho-social factors in the work environment. The diagnostic criteria and prevalence of WMSDs are not well established. In this study, we aimed to determine which WMSDs occur in automotive industry workers and what the underlying risk factors may be. Methods: A cross-sectional study was designed that included 200 automotive industry workers who were diagnosed with a WMSD by physical and radiological examination in the physical therapy and rehabilitation outpatient clinic in the past year. We recorded demographic data, risk factors and WMSD diagnosis names for the patients. Results: In our study, the most common diagnosis was low back disorder (66.5%), followed by neck and shoulder (58%) and upper extremity (23%) disorders. There was a statistically significant increase in the occurrences of shoulder-neck diseases, upper extremity, and low back-lower extremity diseases in workers with inappropriate posture (P < 0.001). Workers who exerted heavy effort or performed repetitive motions were statistically more likely to experience upper extremity disorders (P < 0.001) as well as low back-lower extremity disorders (P = 0.020 and P < 0.001, respectively); there was no statistically significant change in the incidence of shoulder and neck diseases with heavy effort (P = 0.538). Conclusion: WMSD is a serious health and economic problem. In our study, we found that low back and lower extremities and neck and shoulder problems are the most common types of WMSDs in individuals working in the automotive sector. Not using proper posture while working causes health problems in the shoulders, neck, upper extremities and low back and lower extremities. Employees in this sector should be encouraged to use good work ergonomics.